The Relationship Between Ventilation Area and Floor Type with The Incidence of ARI in Toddlers in Pepayungen Angkup Village - Zulfikar Zulfikar; Muzaffar Muzaffar; Andi Pratama Putra; Saipullah Saipullah (Pancasakti Journal Of Public Health Science And Research, 2025)
Acute Respiratory Infection (ARI) in toddlers is an infectious condition that attacks the upper and lower respiratory tract in children under five years of age. This study aims to determine the relationship between ventilation area and floor type with the incidence of ARI in toddlers in Pepayungen Angkup Village. this research is analytic with a cross-sectional design. Data were collected through questionnaires given to 76 respondents using simple random sampling technique. The research was conducted from May 20 to July 03, 2024. Analysis using chi-square test. The results showed that there was a relationship between the area of ventilation with the incidence of ARI in toddlers in the village of Pepayungen angkup with a P value (0.023), and there was a relationship between the type of floor with the incidence of ARI in toddlers in the village of Pepayungen angkup with a P value (0.027). The conclusion in the study shows that environmental conditions, especially ventilation and floor type are factors that need to be considered to prevent the incidence of ARI in toddlers. Suggestions, Improve the quality of home ventilation by ensuring the ventilation area meets health standards, Use more hygienic floor types, such as ceramic or cement floors, to reduce the risk of ARI in toddlers and Educate the public about the importance of a healthy home environment to prevent ARI disease in toddlers.